A review of multimedia usage in embryology education - Abas, Razif; Mohamad Asri, Siti Fadziyah; Saat, Azmah; Mohd Nor, Nurul Huda; Hod, Rafidah; Mohd Nizam, Diana N; Syawalina Omar, Noorkardiffa (Faculty of Information Science and Technology Universiti Kebangsaan Malaysia, 2021)
Embryology, which is a part of anatomy curriculum, is well known to be most difficult to teach. Applied embryology is important in medical practice especially in obstetrics and gynecology. To support teaching embryology, a few multimedia methods have been introduced for the past twenty years, such as animations, two dimensional illustrations, three-dimensional illustrations, movies, and video. Innovative anatomy teaching and learning technology, particularly in the embryology syllabus, dramatically boosts students’ understanding and interest while also indirectly simplifies anatomists’ job. Students are excited to be able to visualize the embryo changes at any gestational age from fertilization to fetus development. Students’ motivation is increased, and their comprehension and memorization are improved. In this review, we elaborate on the details of multimedia methods used for embryology teaching and learning as an alternative to traditional lectures and tutorials. The variety of approaches aids in reducing boredom and maintaining high levels of concentration. As a result, the multimedia usage is useful for long-term memorization.